Avatars and Embodied Agents in Experimental Information Systems Research: A Systematic Review and Conceptual Framework - Aljaroodi, Hussain M.; Adam, Marc T. P.; Chiong, Raymond; Teubner, Timm (Australasian Journal of Information Systems, 2019)
Computerised graphical representations of human users and computer agents, known as avatars and embodied agents, have been extensively explored and investigated in Information Systems (IS) research and practice. Such digital representations can be employed in either 2D or 3D. In order to facilitate research on user and agent representations and their applications in IS, we conduct a systematic literature review and establish the current state of research on humans’ perceptions and behaviours when interacting with avatars and embodied agents. Our findings are based on an analysis of 90 articles published in top outlets in the IS field. This review identifies 1) different types of avatar and embodied agent-mediated interactions with users, 2) current application domains of such representations, 3) their dimensionality, 4) affected psychological constructs, and 5) practical considerations for the design of such digital representations. Finally, we discuss limitations of current research and, based on these, directions for future work.